2021
DOI: 10.1182/bloodadvances.2021005538
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax and azacitidine compared with induction chemotherapy for newly diagnosed patients with acute myeloid leukemia

Abstract: Venetoclax (ven) + azacitidine (aza) is the standard of care for newly-diagnosed acute myeloid leukemia (AML) patients who are not candidates for intensive chemotherapy (IC). Some patients who are IC candidates instead receive ven/aza. We retrospectively analyzed newly-diagnosed AML patients who received ven/aza (N=143) or IC (N=149), to compare outcomes and seek variables that could predict response to one or the other therapy, and ascertain whether treatment recommendations can be refined. The response rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 45 publications
3
80
1
Order By: Relevance
“…Other single center studies have shown similar outcomes as our study including Salhotra et al 34 (mOS, 11 vs 10 months for ven/aza vs CPX-351, respectively; P = .76) in 50 patients at City of Hope, and Asghari et al 35 (mOS, 14 vs 11 months for ven/aza vs CPX-351, respectively; P = .82) in 199 patients at Moffitt Cancer Center and Memorial Healthcare System. Other efforts to compare venetoclax and HMA with intensive chemotherapy are also emerging and require careful comparison, or adjustment, of baseline characteristics to overcome confounding by indication 14 and rate of transplant in both groups. This study was not designed to assess the impact of initial treatment on transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other single center studies have shown similar outcomes as our study including Salhotra et al 34 (mOS, 11 vs 10 months for ven/aza vs CPX-351, respectively; P = .76) in 50 patients at City of Hope, and Asghari et al 35 (mOS, 14 vs 11 months for ven/aza vs CPX-351, respectively; P = .82) in 199 patients at Moffitt Cancer Center and Memorial Healthcare System. Other efforts to compare venetoclax and HMA with intensive chemotherapy are also emerging and require careful comparison, or adjustment, of baseline characteristics to overcome confounding by indication 14 and rate of transplant in both groups. This study was not designed to assess the impact of initial treatment on transplant.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence of successful allogeneic transplant after initial treatment with ven/aza, 13 and recent observational studies comparing venetoclax and azacitidine to 7 + 3 also show similar survival with transplant. 14 Comparative data for CPX-351 vs ven/aza is lacking. Clinicians often rely on local practice patterns, hypotheses about molecular subsets that may benefit from 1 type of treatment, or other subjective factors to choose induction therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Venetoclax has been shown to be effective against AML with IDH1/IDH2 or RUNX1 mutations in vitro. This was confirmed in the Viale-A study, and in another retrospective study which showed that IDH and RUNX1 mutations were predictors of treatment response after combination therapy with venetoclax and AZA [ 16 , 94 , 95 ]. Although VEN is considered to be an alternative to conventional cytotoxic chemotherapy for unfit AML patients, more cases must be examined to determine whether VEN is a viable alternative to the so-called ‘3 + 7′ in fit AML patients.…”
Section: Non-genetic-targeted Strategies For Amlmentioning
confidence: 61%
“…Therefore, we determined the demethylation influence on cell lines with bisulfite modification, followed by PCR and sequencing, which is the most effective method for the high-resolution methylation mapping of genomes ( 28 ). As a DNA methyltransferase inhibitor, 5-AZA is a clinically used epigenetic agent that induces promoter demethylation and gene re-expression AML ( 29 , 30 ). It confirmed that the methylation level of SPERD1 is negatively correlated with mRNA or protein level, and after treatment of 5-AZA, the mRNA and protein levels of SPRED1 increased significantly.…”
Section: Discussionmentioning
confidence: 99%